TGF-β/Smad signaling in renal fibrosis - Meng, Xiao-Ming; Tang, Patrick Ming-Kuen; Li, Jun; Lan, Hui Yao (Frontiers in Physiology, 2015)
TGF-β (transforming growth factor-β) is well identified as a central mediator in renal fibrosis. TGF-β initiates canonical and non-canonical pathways to exert multiple biological effects. Among them, Smad signaling is recognized as a major pathway of TGF- signaling in progressive renal fibrosis. During fibrogenesis, Smad3 is highly activated, which is associated with the down-regulation of an inhibitory Smad7 via an ubiquitin E3-ligases-dependent degradation mechanism. The equilibrium shift between Smad3 and Smad7 leads to accumulation and activation of myofibroblasts, overproduction of ECM (extracellular matrix), and reduction in ECM degradation in the diseased kidney. Therefore, overexpression of Smad7 has been shown to be a therapeutic agent for renal fibrosis in various models of kidney diseases. In contrast, another downstream effecter of TGF-β/Smad signaling pathway, Smad2, exerts its renal protective role by counter-regulating the Smad3. Furthermore, recent studies demonstrated that Smad3 mediates renal fibrosis by down-regulating miR-29 and miR-200 but up-regulating miR-21 and miR-192. Thus, overexpression of miR-29 and miR-200 or down-regulation of miR-21 and miR-192 is capable of attenuating Smad3-mediated renal fibrosis in various mouse models of chronic kidney diseases. Taken together, TGF-/Smad signaling plays an important role in renal fibrosis. Targeting TGF-β/Smad3 signaling may represent a specific and effective therapy for chronic kidney diseases associated with renal fibrosis.